Third stage of labor assisted with intraumbilical oxytocin: expectant and routinary - Vilchez, Rosa Gutarra (2013)
Objectives: To determine efficacy and safety of assisted third stage of labor using intraumbilical oxytocin or either expectant or routinary. Design: Clinical controlled trial. Location: Hospital Vitarte, Ministerio de Salud, Lima Peru. Participants: Women in third stage of labor. Interventions: One hundred and eighty laboring women were randomized by systematic sampling when admitted for hospitalization. Three ways of third stage of labor management were compared: a) assisted, using intraumbilical oxytocin; b) expectant with partial clamping of the umbilical cord (by clamping only the fetal end of the umbilical cord); and c) routinary or expectant with double clamping of the umbilical cord. 60 pregnant women were randomized to each group. Main outcome measures: Duration of the third stage of labor, prepartum and 24 hours postpartum hematocrit, complications. Results: There was a significant reduction in the time of the third stage of labor and in the variation of the hematocrit values with the assisted management and the expectant method compared to routine management in patients who did not have episiotomy. There were no significant differences in puerperal hemorrhage. Conclusions: Assisted and expectant management of the third stage of labor were more efficacious compared to routine management of the third stage of labor. Safety was similar in the three groups studied.Key words: Third stage of labor, assisted, expectant and routinary management.